(3GdJMaI GdTGgjI (B( (3aj GdgjFI GdLSeGfjI (B)s - (3eMehO Hf eSYhO Hf eUdM GdaGQSj GdYdGej , bWH GdOjf , GdbWH GdTjQGRj,J (B710 (3g` s ((3eOjfI GdSeGhI s)
(3ChdgG (B:s
(3NjQ GdeHGOF eGRjf HGdMeO CeG HYO , aEf eMehO Hf eSYhO jbhd (B: (3dhdG Gf GdSGOI ShZJ ddCUGZQ GdCfHSGW Edi GdCcGHQ QCjJ Cf CJMa ENJQJ efg Yde GdgjFI s
(3BNQgG (B:s
(3hjbSe gPG GdYOO Ydi YOO eKGd eGajgG Ef cGf CUZQ efgG , aeG HdZ Ch NQL jchf YOO CeKGd eG ajg ef ecYH Gdejd hGdMeOddg agPG eG SeMJ HYbQjMJi LYdJg NOeI deYehQ NRGfI Gdehdi GdeYXe s
(3HgG CTcGds
(3HChdgG agQS ddehVhYGJ HNW GdfGSN faSgs
(3CJe GdeDda JCdjag ai eOjfI SjhGS SfI (B684 (3g`s
(3fbdgG GdfGSN Yf fSNI cJHJ SfI (B830 (3g` Yf fSNI GdCUd s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3Gdadcs